2014
DOI: 10.1016/j.ssc.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Topological insulator based spin valve devices: Evidence for spin polarized transport of spin-momentum-locked topological surface states

Abstract: Spin-momentum helical locking is one of the most important properties of the nontrivial topological surface states (TSS) in 3D topological insulators (TI). It underlies the iconic topological protection (suppressing elastic backscattering) of TSS and is foundational to many exotic physics (eg., majorana fermions) and device applications (eg., spintronics) predicted for TIs. Based on this spin-momentum locking, a current flowing on the surface of a TI would be spin-polarized in a characteristic in-plane directi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 40 publications
5
64
0
Order By: Relevance
“…This current induced spin polarization of the SS, controllable by the magnitude and the direction of the current, can be used to torque a ferromagnet (FM) [4,5]. In recent experiments [7][8][9][10][11][12][13][14][15][16][17][18][19], the spin accumulation on the surface of 3D TIs Bi 2 Se 3 , (Bi x Sb 1−x ) 2 Te 3 , Bi 1.5 Sb 0.5 Te 1.7 Se 1.3 , BiSbTeSe 2 , Bi 2 Te 2 Se and Sb 2 Te 3 , mostly grown by molecular beam epitaxy (MBE) or exfoliated, were electrically measured by the voltage probed with FM contact, where the voltage depends on the projection of SS spin polarization onto the FM magnetization direction.In this work, we detect the current induced spin polarization on the surface of an MBE grown Bi 2 Te 3 thin film using Fe contact deposited on the surface and separated by a thin MgO barrier. We also provide a theoretical estimate of the detected spin signal, i.e., the voltage probed with the FM contact.…”
mentioning
confidence: 99%
“…This current induced spin polarization of the SS, controllable by the magnitude and the direction of the current, can be used to torque a ferromagnet (FM) [4,5]. In recent experiments [7][8][9][10][11][12][13][14][15][16][17][18][19], the spin accumulation on the surface of 3D TIs Bi 2 Se 3 , (Bi x Sb 1−x ) 2 Te 3 , Bi 1.5 Sb 0.5 Te 1.7 Se 1.3 , BiSbTeSe 2 , Bi 2 Te 2 Se and Sb 2 Te 3 , mostly grown by molecular beam epitaxy (MBE) or exfoliated, were electrically measured by the voltage probed with FM contact, where the voltage depends on the projection of SS spin polarization onto the FM magnetization direction.In this work, we detect the current induced spin polarization on the surface of an MBE grown Bi 2 Te 3 thin film using Fe contact deposited on the surface and separated by a thin MgO barrier. We also provide a theoretical estimate of the detected spin signal, i.e., the voltage probed with the FM contact.…”
mentioning
confidence: 99%
“…An essential feature of these TI surfacestates is helical spin-momentum locking due to strong spinorbit interactions, which provides near-ideal transduction between spin and charge transport, making Tis promising material for spintronic applications [1][2][3]. An applied charge current induces a net spin polarization/accumulation at the TI surface, which can be controlled by the amplitude and the polarity of the current [4][5][6][7][8][9][10][11][12][13][14][15]. For example, choosing the x and y directions along the TI surface and the z direction pointing away from the TI, electron flow in the negative x direction within either conduction or valence band surface states results in a net electron spin in the positive y direction.…”
mentioning
confidence: 99%
“…Low temperature magneto-transport measurements have been performed by several groups using stack(s) of molecular beam epitaxy (MBE) grown ferromagnetic metal (FM) layers either on TI flakes or on MBE-grown TIs [11][12][13][14]. These groups have used Bi2Se3 or BiSbTe TIs and Fe, Co or Py FMs.…”
mentioning
confidence: 99%
“…Indeed, the spin momentumlocking phenomenon, which is known as the unique property of TI surface state, is detected in the Ni/Bi 2 Se 3 hybrid structure as shown in Ref. [20], implying that the surface state of TI is survived at Ni/Bi 2 Se 3 interface. Furthermore, it was reported that the spin direction for the magnetic atom on the TI surface tend to orient out-of-plane direction due to the strong spin-orbit interaction.…”
Section: Methodsmentioning
confidence: 92%
“…Meanwhile, various types of structures containing the ferromagnet/TI interface have been fabricated and used to identify unique spin phenomena of the TI surface states. 11,[19][20][21][22] The ferromagnetic layer interfaced with TI was simply used to detect the spin direction of the carriers in those structures. The precise information of the magnetic properties of ferromagnetic layer that interfaced with the TI surface is, however, prerequisite for the investigation of the spin phenomena in the ferromagnet/TI system.…”
Section: Introductionmentioning
confidence: 99%